O caso do programa mulheres sim do IFSC - Michels, Juliana Pereira (2018)
Until recently, the concept of innovation has been linked almost exclusively to the technological domain and the competitive logic of the market. However, in recent years, in academic debate and in social life, innovative actions have been gaining ground in order to generate inclusive and transformative processes in society. From this perspective, the role of public educational institutions in the promotion of social innovation programs aimed at people in situations of social vulnerability through extension is perceptible. In view of the above, the objective of this work is to analyze the Women Sim extension program, developed by the Federal Institute of Santa Catarina, as social innovation. To this end, the study sought to investigate the determinants of social innovation in the institution under investigation, focusing on the objective of this type of innovation: inclusion, empowerment and autonomy. The research is characterized as a case study, with a qualitative approach, of descriptive and exploratory nature. Data were collected through documentary research, participant observation and semi-structured interview, and a content analysis was developed. The results achieved by the program can be listed as income generation, personal and professional growth, the desire to resume studies, increase self-esteem, insertion in the world of work, recognition of rights and awareness of inequalities of power. With regard to the characteristics of social innovation evidenced in the theoretical framework, the following are observed in Women Yes: it emerged as one of the viable alternatives to face a need of society, there is participation and collaboration of the involved actors, the formation of new relations social, collective learning process, training and generation of new knowledge, and, more importantly, resulted in higher levels of social inclusion, autonomy and empowerment. Thus, one can affirm that according to the characteristics listed, the Women Yes program is characterized as a practice of social innovation.